Comparison of Deformation Vectors Due to Earthquake in Subduction Zone and Sumatran Fault for Each Phase of Earthquake Cycle - Fadilla Monica; Vira Friska; Deasy Arisa; Marzuki Marzuki (Jurnal Ilmu Fisika, 2022)
This study compares the deformation in West Sumatra due to the earthquakes in the subduction zone and the Sumatran Fault. The Mw6.0 Mentawai earthquake 2019 with a thrust fault mechanism and the Mw5.4 South Solok earthquake 2019 with a strike-slip fault mechanism were used as case studies for the subduction zone and Sumatran Fault, respectively. The deformation was observed using 12 SuGAr (Sumatra GPS Array) and 8 InaCORS (Indonesian Continuously Operating Reference Station) stations, which were processed using GAMIT/GLOBK software. There are differences in the deformation vectors of the two earthquakes. The Mentawai earthquake experienced larger energy accumulation than the South Solok earthquake. The coseismic phase of the Mentawai earthquake experienced the largest horizontal shift at the SLBU station, which was 15.48 mm in the direction of S29.96W, while the South Solok earthquake is found to horizontally shift the CSDH station at the size of 5.75 mm towards S11.45E. The postseismic phase of the Mentawai earthquake lasted 60 days, longer than the South Solok earthquake (20 days). The difference in deformation characteristic between these two earthquakes found in this study will be valuable information in modeling earthquakes in Sumatra.